MEMBANGUN JARINGAN EKOWISATA BERKELANJUTAN DI BALI (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2013)
The identification toward of problems of tourism development in the four villages that are the member of JED is an interesting recent issues to be studied, because it can be the reason of emergence the Jed as well as a reference or a fundamental to the next research project in determine about how the application of ecotourism principles at pelaga village, sibetan village, tenganan village, and ceningan, which as the final result is to formulated the model of sustainable ecotourism as the goal of JED.Based on the research result, the impact of tourism development in these village already feel by the local communitiies. The tourism development impacts in the villages ecologically are not yet emerging the negative impact significanly it can be proved by the retaining of enviromental conservation and the absence of land use in each villages who are the member of JED. The community of the villages get a positive benefit in social economic, it can be seen there is an opportunity to get a new job and wider the bussines opportunity . the impact of social culture in this villages is retaining of local culture that can be seen in tenganan village which the community has an efforts to strenghten the local community identity.